2016
DOI: 10.18632/oncotarget.10295
|View full text |Cite
|
Sign up to set email alerts
|

TP53 codon 72 polymorphism may predict early tumour progression in paediatric pilocytic astrocytoma

Abstract: Pilocytic astrocytoma and ganglioglioma may occur in inaccessible or surgically difficult areas. In case of incomplete resection, the availability of biological predictors of tumour progression could be particularly important. To this end, an analysis of p53 codon 72 polymorphism and assessment of its role as prognostic marker were performed.The status of the p53 Arg72Pro polymorphism was evaluated by pyrosequencing method in a multicenter cohort of 170 paediatric patients. Genotype/phenotype associations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…In one case of PLNTY with malignant transformation, TP53 mutation was observed 6 . As in our elderly case, it has been suggested that p53 abnormality could be involved in tumor recurrence and malignant transformation of low‐grade glioneuronal tumor/glioma 27,28 . PLNTY has been established as an independent disease concept, but its methylation profile is closest to ganglioglioma 14,29 .…”
Section: Discussionsupporting
confidence: 50%
“…In one case of PLNTY with malignant transformation, TP53 mutation was observed 6 . As in our elderly case, it has been suggested that p53 abnormality could be involved in tumor recurrence and malignant transformation of low‐grade glioneuronal tumor/glioma 27,28 . PLNTY has been established as an independent disease concept, but its methylation profile is closest to ganglioglioma 14,29 .…”
Section: Discussionsupporting
confidence: 50%
“…Pro72 allele has been implicated in coronary artery disease (Khan et al, 2016 ), systemic lupus erythematosus (Lee et al, 2012 ) and ulcerative colitis (Vaji et al, 2011 ). In contrast, Arg72 allele is implicated in pilocytic astrocytoma (Mascelli et al, 2016 ). Codon 72 TP53 polymorphisms have shown different associations with the risk of carcinomas in different populations, including oral carcinoma susceptibility (Tandle et al, 2001 ; Nagpal et al, 2002 ; Hsieh et al, 2005 ; Wang et al, 2012 , 2014 ; Dahabreh et al, 2013 ; Saleem et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…The potential effect of sex-specific genotype has also been studied in pediatric brain tumors. Polymorphic variants across genes have been shown to modify the risk and development of pediatric brain tumors [ 116 , 117 ]. Glutathione S-transferase mu 1 gene deletion and its dual deletion with the glutathione S-transferase theta 1 gene were found to be strongly associated with brain tumor in males, including tumors of glial origin.…”
Section: Disease Phenotypementioning
confidence: 99%